Analyzing Public Transportation for the Effects of Individual Characteristics on Mode Choice with Multi Agent Simulation. (2016) - Oral, L. Özge; Tecim, Vahap
Abstract: The movements of modes of transport in network can be analyzed with micro-simulation method. As the development of computers the micro-simulation methods such as multi-agent systems become more popular in transportation analysis. In this study, the problem of individual and trip characteristics on the mode choice are effective or not, is solved. Network, facilities, daily travel plans and transport vehicles were accepted as an agent. Considering parameters that will be effective in mode choice, how transportation road network is distributed spatially, how the personal and trip characteristics of trip makers effects on mode choice spatially were analyzed in study area. As a result of this study, personnel and trip characteristics of trip makers are affected on different transportation mode.